Plant growth and symptomatology of macronutrient deficiencies in cowpea plants - Eduardo Melo Santiago, Franklin; Louzeiro de Aguiar Santiago, Flávia; Ferreira Lustosa Filho, José; Felippe Ratke, Rafael (Comunicata Scientiae, 2018)
Cowpea is a widely grown annual legume in the North and Northeast regions of Brazil. It is one of the main sources of protein and income for the populations of these regions. However, few studies have shown the nutritional requirements, and symptomatology of nutritional deficiencies of cowpea cultivars. In this context, the objective of this work was to evaluate the initial growth and symptomatology of macronutrient deficiencies in cowpea plants of the BR17-Gurguéia cultivar. A randomized complete experimental design with three replications was used, with seven treatments consisted of nutrient solutions containing no N, P, K, Ca, Mg, or S, and a nutrient solution containing all macro and micronutrients as control, using one plant per plot. Plant height, stem diameter, number of leaves, leaf area, root volume, and shoot and root dry weights were evaluated, and visual symptoms of nutritional deficiencies were described at 30 days after planting. Nitrogen, phosphorus, potassium, calcium, and magnesium were the most limiting nutrients for the vegetative growth and biomass production of cowpea up to 30 days of cultivation. The absence of these elements in the nutrient solution caused morphological changes and visual symptoms that are characteristic of the nutritional deficiency of these nutrients.